Modeling the influence of external heat flux on thermal characteristics of the silica aerogel/paraffin in a cylindrical atomic duct - Lishan Geng; Ali B.M. Ali; Shahram Babadoust; Anjan Kumar; Barno Abdullaeva; Rasha Abed Hussein; Soheil Salahshour; Sh Esmaeili (Case Studies in Thermal Engineering)
As the price of fuel rises and the environmental impact of greenhouse gases intensifies, a larger population is opting for alternative sources of sustainable energy. Currently, scientists are facing challenges in discovering an energy-saving method that is effective in diverse scenarios and is user-friendly. Many individuals are interested in using materials that can transition between solid, liquid, and gas states. The objective was to use these materials for heat retention. Silica aerogels exhibit effective thermal regulation, regardless of whether the environment is hot or cold. Phase change materials are substances that store thermal energy effectively and play a crucial role in maintaining temperature stability. This research explored how external heat flux affected the behavior of a tube filled with silica aerogel and phase change materials. Additionally, we incorporated CuO nanoparticles to evaluate their impact on the system. The study utilized LAMMPS software to perform molecular dynamics simulations for this purpose. To achieve our goal, we evaluated various aspects of virtual structure, which can be influenced by factors, such as density, velocity, temperature profile, heat flux, thermal conductivity, and the duration of filling and emptying. The findings indicate that as external heat flux increased, maximum density decreased to 0.1364 atoms/Å³. Conversely, thermal conductivity, maximum velocity, and temperature increase to 1.97 W/m·K, 0.0138 Å/fs, and 649 K, respectively. Also, with maximum external heat flux, charging time decreases to 5.94 ns, while discharge time is recorded at 8.56 ns. Increased external heat flux resulted in greater thermal energy transfer to the material, causing the atoms to vibrate more vigorously and collide more frequently.